Mediating Clinical Claims - Allen, Tony, Mr (Bloomsbury Professional, 2018)
"Mediating Clinical Claims is a timely and detailed look at the growing practice of mediating clinical negligence claims in England, written by one of the UK's most experienced mediators of clinical claims. The book is aimed at all those with an interest in understanding why and how mediation is such an effective process in resolving such claims - claimants, healthcare professional and managers, lawyers, judges, policy-makers and mediators. It reviews research on what claimants and clinicians really want from healthcare complaints and claims. It offers help on how best to prepare for and conduct such mediations, giving numerous anonymised examples based on real mediations. This new title looks at How mediation of clinical claims has developed How mediation differs from other processes Practical guidance for all participants The legal framework in which such mediation operates The law and practice of clinical claims Process design and the special problems of multi-party claims Data security and classification Protecting organisations Future developments."--Bloomsbury Publishing.